2020
DOI: 10.18657/yonveek.543841
|View full text |Cite
|
Sign up to set email alerts
|

Kurumsal Kimlik Oluşturmada Kurumsal İmaj Algısının Rolü: Örgüt Kültürünün Aracılık Etkisi

Abstract: Bu çalışmada kurumsal bir kimlik oluşturabilme çabası için kurumsal imaj algısının önemi ve kurumsal kimlik ile kurumsal imaj ilişkisinde örgüt kültürünün aracılık etkisinin tespit edilmesi amaçlanmıştır. Bu amaç doğrultusunda yüksek öğretim kurumlarının iç paydaşlarının kurumsal imaj, kurumsal kimlik ve örgüt kültürü algılarının ortaya konulmasına yönelik nicel bir araştırma yapılmıştır. Araştırmaya veri toplamak için Muş Alparslan Üniversitesi'nin iç paydaşlarına bir anket çalışması uygulanmıştır. Elde edile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Rajkumar (2020) also revealed that fear, anxiety and stress severely increase during an outbreak and when the number of cases increases (Rajkumar, 2020; Johnson and Indvik, 1997; Handrich, 2000). At a time when news about the pandemic is frequently made in the media, cases of mental health deterioration are more common in individuals with high levels of depression (Roy et al , 2020, Çiçek and Almalı, 2020; 246). During an outbreak threat, symptoms such as post-traumatic stress reactions, depressive symptoms and anxiety disorder symptoms reach a clinical level (Shultz et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rajkumar (2020) also revealed that fear, anxiety and stress severely increase during an outbreak and when the number of cases increases (Rajkumar, 2020; Johnson and Indvik, 1997; Handrich, 2000). At a time when news about the pandemic is frequently made in the media, cases of mental health deterioration are more common in individuals with high levels of depression (Roy et al , 2020, Çiçek and Almalı, 2020; 246). During an outbreak threat, symptoms such as post-traumatic stress reactions, depressive symptoms and anxiety disorder symptoms reach a clinical level (Shultz et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of some psychological symptoms, defined as acute stress response, after the COVID-19 pandemic is considered as “usual reactions to the unusual situation” (Işıklı, 2020, p. 6–7). The belief in self-efficacy affects one’s life choices, motivation level, quality of functioning, resistance to adversity, vulnerability to stress and depression (Bandura, 1994; Çiçek and Almalı, 2020, p. 246). The studies of Malik et al (2011) and Hammad et al (2012) found that stress is the main factor in the disruption of the work of employees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation